2018
DOI: 10.3389/fmicb.2017.02528
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Fungal Bioremediation of Acidic Radioactive Waste Sites: Characterization and Genome Sequence of Rhodotorula taiwanensis MD1149

Abstract: Highly concentrated radionuclide waste produced during the Cold War era is stored at US Department of Energy (DOE) production sites. This radioactive waste was often highly acidic and mixed with heavy metals, and has been leaking into the environment since the 1950s. Because of the danger and expense of cleanup of such radioactive sites by physicochemical processes, in situ bioremediation methods are being developed for cleanup of contaminated ground and groundwater. To date, the most developed microbial treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 73 publications
(92 reference statements)
1
26
0
Order By: Relevance
“…Melanized fungi have generated interest due to their abundance in environments with high levels of background IR, which has raised the possibility of using melanin for radiation protection, or discovering a compound produced by these organisms that could prevent radiation damage or aid in recovery from radiation damage in human tissues (Dadachova et al, 2007;Cordero, 2017;Pacelli et al, 2017). Many fungi, melanized and non-melanized, are also extraordinarily resistant to acute and chronic IR, suggesting that mechanisms for radiation recovery remain to be discovered by characterizing the response to IR in these organisms (Holloman et al, 2007;Jung et al, 2016;Shuryak et al, 2017;Jiang et al, 2018;Tkavc et al, 2018). Previously, the transcriptomic responses of C. neoformans (Jung et al, 2016), W. dermatitidis (Robertson et al, 2012), S. pombe (Watson et al, 2004) and S. cerevisiae (Kimura et al, 2006) to various doses of γ-radiation have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Melanized fungi have generated interest due to their abundance in environments with high levels of background IR, which has raised the possibility of using melanin for radiation protection, or discovering a compound produced by these organisms that could prevent radiation damage or aid in recovery from radiation damage in human tissues (Dadachova et al, 2007;Cordero, 2017;Pacelli et al, 2017). Many fungi, melanized and non-melanized, are also extraordinarily resistant to acute and chronic IR, suggesting that mechanisms for radiation recovery remain to be discovered by characterizing the response to IR in these organisms (Holloman et al, 2007;Jung et al, 2016;Shuryak et al, 2017;Jiang et al, 2018;Tkavc et al, 2018). Previously, the transcriptomic responses of C. neoformans (Jung et al, 2016), W. dermatitidis (Robertson et al, 2012), S. pombe (Watson et al, 2004) and S. cerevisiae (Kimura et al, 2006) to various doses of γ-radiation have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Biosurfactants offer a more environmentally friendly option (biodegradable and petroleum-independent); however, there are a limited number of commercially available biosurfactants, and each one covers only a small portion of the HLB scale. Therefore, in order to expand PEFA coverage on the HLB scale, it was recently published that a new strain of Rhodotorula taiwanensis produced hypoacetylated PEFA compounds compared to those produced by Rhodotorula babjevae [108,109]; the difference in their acetylation profiles resulted in different surface tension of the growth medium, i.e. a different hydrophilic-lipophilic balance.…”
Section: Rhodotorula Babjevae and Rhodotorula Taiwanensismentioning
confidence: 99%
“…The result can also be compared with the report of Chen et al [22] which identified 17 yeast strains and found them to be capable of growing in bile salt solutions and most of them tolerated low pH, surviving in gastric juice. This can be related to the results of Sridevi et al [23] where species of Rhodotorula and Candida tolerated low pH [24]. The potential of these isolates to withstand stress of the GIT and colonise it, is very essential to their being considered as probiotic organisms.…”
Section: Acid Tolerance At Ph 30 Under Acidic Condition In Hcl Solutionmentioning
confidence: 63%